Determination of a prediction model for therapeutic response and prognosis based on chemokine signaling-related genes in stage I–III lung squamous cell carcinoma - Lai, Jinzhi; Yang, Shiyu; Chu, Shuqiang; Xu, Tianwen; Huang, Jingshan (Frontiers in Genetics, 2022)
Background: The chemokine signaling pathway plays an essential role in the development, progression and immune surveillance of lung squamous cell carcinoma (LUSC). Our study aimed to systematically analyze chemokine signaling-related genes (CSRGs) in LUSC patients with stage I-III and develop a prediction model to predict prognosis and therapeutic response. Methods: A total of 610 LUSC patients with stage I-III disease from 3 independent cohorts were included in our study. LASSO and stepwise multivariate Cox regression analyses were used to develop a CSRG-related signature. GSVA and GSEA were performed to identify potential biological pathways. The ESTIMATE algorithm, ssGSEA method and CIBERSORT analyses were applied to explore the correlation between the CSRG signature and the tumor immune microenvironment. The TCIA database and pRRophetic algorithm were utilized to predict responses to immunochemotherapy and targeted therapy. Results: A signature based on three CSRGs was developed in the TCGA training set and validated in the TCGA testing set and GEO external validation sets. A Kaplan‒Meier survival analysis revealed that patients in the high-risk group had significantly shorter survival than those in the low-risk group. A nomogram combined with clinical parameters was established for clinical OS prediction. The calibration and DCA curves confirmed that the prognostic nomogram had good discrimination and accuracy. An immune cell landscape analysis demonstrated that immune score and immune-related functions were abundant in the high-risk group. Interestingly, the proportion of CD8 T cells was higher in the low-risk group than in the high-risk group. Immunotherapy response prediction indicated that patients in the high-risk group had a better response to CTLA-4 inhibitors. We also found that patients in the low-risk group were more sensitive to first-line chemotherapeutic treatment and EGFR tyrosine kinase inhibitors. In addition, the expression of genes in the CSRG signature was validated by qRT-PCR in clinical tumor specimens. Conclusion: In this study, we developed a CSRG-related signature that could predict prognosis and sensitivity to immunochemotherapy and targeted therapy in LUSC patients with stage I-III disease. Our study provides insight into the multifaceted role of the chemokine signaling pathway in LUSC and may help clinicians implement optimal individualized treatment for patients.